Improving students’ reading comprehension of exposition text by using multipass strategy - Rika Indah Sari (Relawan Jurnal Indonesia, 2022)
The goal of this research was to see if there was a significant difference in reading comprehension between students who were taught using the Multipass technique and those who were not. The participants of this study were from SMA Negeri 2 Tanjung Raja in the eleventh grade. The data was gathered through a written test. The T-test was employed to analyze the data. The value of t-obtained was 4.4790 at the significant level of p<0.05 and the degree of freedom (df) was 62, according to the results of the independent sample test. Because the value of t-obtained (4.4790) was higher than the critical value of t-table (2.000), it was determined that there was a significant difference in reading comprehension achievement between students who were taught English reading comprehension using the Multipass technique. By employing the Multipass strategy, students can improve their reading comprehension of expository text.